ANALISIS KEABSAHAN KEPUTUSAN GUBERNUR JAWA TENGAH NOMOR 660.1/6 TAHUN 2017 TENTANG IZIN LINGKUNGAN KEGIATAN PENAMBANGAN DAN PEMBANGUNAN PABRIK PT SEMEN INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Arief Hidayat; Ahmad Redi (Jurnal Hukum Adigama, 2018)
The State of Indonesia is a State of Law. But, in fact the ideals of the idea of the State of Law that was built by developing the legal tool itself as a system that is functional and just to achieve community welfare and social justice has not been optimally done. This is reflected in the new Environmental Permit issued by Central Java Governor Ganjar Pranowo (No. 660.1 / 6 of 2017 on Environmental Permit for Mining and Construction Activities of PT Semen Indonesia Plant) is considered to have injured the ideals of the law itself. The new Environmental Permit is contradictory to the content of the Review Judgment issued by the Supreme Court (Supreme Court Verdict Decision Number 99 PK / Tun 2016), because in the ruling it ordered that the Governor Replace the old Environmental Permit, which was issued in 2012 and did not issue New Environmental Permit. The verdict contains the basis of judges' consideration in deciding cases that have reflected fairness and legal certainty. The result of the research on the validity of the Environmental Permit Decree on the Review Judgment issued by the Supreme Court concluded that the decree should be invalid because it is not in line with the decision of the court which has permanent legal force.